2015
DOI: 10.1038/nprot.2015.079
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microfluidics to control and measure signaling dynamics in single yeast cells

Abstract: Microfluidics coupled to quantitative time-lapse fluorescence microscopy is transforming our ability to control, measure, and understand signaling dynamics in single living cells. Here we describe a pipeline that incorporates multiplexed microfluidic cell culture, automated programmable fluid handling for cell perturbation, quantitative time-lapse microscopy, and computational analysis of time-lapse movies. We illustrate how this setup can be used to control the nuclear localization of the budding yeast transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 79 publications
(142 reference statements)
0
91
0
Order By: Relevance
“…3). In response to ROS stress, Msn2/4 accumulated in the nucleus, where they promoted transcriptional activation of stress‐responsive genes (Hansen et al ., 2015; Yi and Huh, 2015). However, deletion of MrMsn2 increased production of ROS (data not shown) and upregulated expression of antioxidant genes to protect against ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In response to ROS stress, Msn2/4 accumulated in the nucleus, where they promoted transcriptional activation of stress‐responsive genes (Hansen et al ., 2015; Yi and Huh, 2015). However, deletion of MrMsn2 increased production of ROS (data not shown) and upregulated expression of antioxidant genes to protect against ROS.…”
Section: Discussionmentioning
confidence: 99%
“…They are similar to ScMsn2/4 of Saccharomyces cerevisiae (Schmitt and Mcentee, 1996) and have been characterized in Aspergillus parasiticus , A. flavus , Beauveria bassiana , Magnaporthe oryzae , Metarhizium robertsii and Verticillium dahliae (Chang et al ., 2011; Liu et al ., 2013; Zhang et al ., 2014; Tian et al ., 2017). Under abiotic and biotic stresses, Msn2/4 is phosphorylated for translocation from the cytoplasm to the nucleus, where it drives the transcription of stress‐induced genes (Hansen et al ., 2015; Yi and Huh, 2015; Li et al ., 2017). The underlying mechanism of the regulation of Msn2/4 activity by protein kinase A (PKA), the rapamycin signalling pathway, the Snf1 protein kinase pathway and the high‐osmolarity glycerol (HOG) pathway have been identified (Liu et al ., 2013; Zhang et al ., 2014; Li et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were then immediately imaged using the exact same exposure conditions as described in [6]. Images were then analysed and fluorescence quantified as previously described [6,51]. After quantifying the fluorescence intensity per cell for each of the five genes, we then fitted a simple line to the data and found that each YFP molecule contributed about 100.8 arb.…”
Section: Calibrating Yfp Fluorescence To Absolute Numbers Of Moleculesmentioning
confidence: 99%
“…After quantifying the fluorescence intensity per cell for each of the five genes, we then fitted a simple line to the data and found that each YFP molecule contributed about 100.8 arb. units fluorescence per cell under our excitation settings [51]. We therefore divided the total fluorescence per cell from the previous dataset [6] to obtain the total number of YFP molecules per cell.…”
Section: Calibrating Yfp Fluorescence To Absolute Numbers Of Moleculesmentioning
confidence: 99%
See 1 more Smart Citation